2015
DOI: 10.1007/978-3-319-15554-8_45
|View full text |Cite
|
Sign up to set email alerts
|

Using Linguistic Features to Estimate Suicide Probability of Chinese Microblog Users

Abstract: Abstract. If people with high risk of suicide can be identified through social media like microblog, it is possible to implement an active intervention system to save their lives. Based on this motivation, the current study administered the Suicide Probability Scale(SPS) to 1041 weibo users at Sina Weibo, which is a leading microblog service provider in China. Two NLP (Natural Language Processing) methods, the Chinese edition of Linguistic Inquiry and Word Count (LIWC) lexicon and Latent Dirichlet Allocation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 17 publications
0
58
0
1
Order By: Relevance
“…The instruments used to detect suicidal ideation and the possibility of an individual committing suicide were the Suicide Probability Scale [32,39,48], the Acquired Capability for Suicide Scale [30], and the Interpersonal Needs Questionnaire [30]. Satisfaction with life and well-being were measured with the Satisfaction with Life Scale [28,34], the Positive and Negative Affect Schedule [55], and the Psychological Well-Being Scale [55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The instruments used to detect suicidal ideation and the possibility of an individual committing suicide were the Suicide Probability Scale [32,39,48], the Acquired Capability for Suicide Scale [30], and the Interpersonal Needs Questionnaire [30]. Satisfaction with life and well-being were measured with the Satisfaction with Life Scale [28,34], the Positive and Negative Affect Schedule [55], and the Psychological Well-Being Scale [55].…”
Section: Resultsmentioning
confidence: 99%
“…It is employed to classify the polarity of a given text into categories such as positive, negative, and neutral [77]. Several studies [24,28,30,32,34,39, 49,50,52-55,57,60,65-68,70] used the well-known linguistic inquiry and word count (LIWC) [78] to extract potential signals of mental problems from textual content (eg, the word frequency of the first personal pronoun “I” or “me” or of the second personal pronoun, positive and negative emotions being used by a user or in a post). OpinionFinder [79] was used by Bollen et al [71] and SentiStrength [80] was used by Kang et al [27] and by Durahim and Coşkun [47] to carry out sentiment analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the effect of personality on real life [27], Bai et al has conducted research to predict the Big-Five personality of Chinese Weibo users based on user behaviors at social network sites using the decision tree method [28]. Zhang et al used linguistic features to predict suicide probability of Weibo users through linear regression [29]. Golbeck et al collected information from Twitter and made a prediction of personality using the Gaussian process [30].…”
Section: Cyber Psychometrics Methodsmentioning
confidence: 99%
“…(b) To screen for posts with suicidal ideation, we trained topic models to extract linguistic features for training models. Results indicated that the models can find suicidal posts accurately (Zhang et al, 2015), which have been used to build a system for monitoring suicidal posts in real-time (http://ccpl.psych.ac.cn/suicide/).…”
mentioning
confidence: 99%